Large-Scale Discovery and Validation Studies Demonstrate Significant Reductions in Circulating Levels of IL8, IL-1Ra, MCP-1, and MIP-1β in Patients With Type 1 Diabetes - Purohit, Sharad; Sharma, Ashok; Hopkins, Diane; Steed, Leigh; Bode, Bruce; Anderson, Stephen W.; Reed, John Chip; Steed, R. Dennis; Yang, Tao; She, Jin-Xiong (The journal of clinical endocrinology and metabolism, 2015)
Context:Previous studies have attempted to elucidate the potential role of various cytokines and chemokines in human type 1 diabetes (T1D); however, the precise role of these serum proteins in T1D is still controversial and undetermined primarily due to the small sample sizes of the previous studies. We profiled a panel of serum cytokines and chemokines using a large-scale, two-stage study design for the discovery and validation of the serum proteins associated with T1D.Participants:The participants were patients with T1D and islet autoantibody–negative control subjects from the Phenome and Genome of Diabetes Autoimmunity study.Main Outcome Measures:Thirteen cytokines and chemokines were measured in serum of 4424 subjects using multiplex immunoassays.Results:Using 1378 samples in Stage 1, we found that four of the 13 proteins are significantly lower in patients with T1D than controls (IL8: odds ratio [OR] = 0.40; P = 5.7 × 10−19; IL-1Ra: OR = 0.42; P = 1.1 × 10−13; MCP-1: OR = 0.60; P = 6.7 × 10−9; and MIP-1β: OR = 0.63; P = 4.2 × 10−7). Our confirmation data with 3046 samples in Stage 2 further confirmed the significant negative associations of these four proteins with T1D (IL8: OR = 0.43; P = 8.9 × 10−32; IL-1Ra: OR = 0.56, P = 3.7 × 10−27; MCP-1: OR = 0.61, P = 4.3 × 10−17; and MIP-1β: OR = 0.69, P = 2.4 × 10−13). Quartile analyses also suggested that significantly more T1D cases have protein levels in the bottom quartile than in the top quartile for all four proteins: IL8 (OR = 0.09), IL-1Ra (OR = 0.18), MCP-1 (OR = 0.38), and MIP-1β (OR = 0.44). Furthermore, the negative associations between T1D and serum levels of all four proteins are stronger in genetically high-risk groups compared with the moderate and low-risk groups.Conclusions:IL8, IL-1Ra, MCP-1, and MIP-1β are significantly lower in patients with T1D than controls.